A Methods engineering study on Metro Biscuit Corporation - Juadiong, Michael Robert M.; Lopez, Ana Camille D.; Lu, Raymond Daniel A.; Torres, Jacqui Belle E. (College of Engineering, 2005)
This methods engineering study was conducted on Metro Bisquit Corporation, a manufacturer of biscuits and candies. It was aimed at improving its existing methods, working conditions, and facility layout to help increase productivity without sacrificing worker welfare and safety. Plant visits were held to help gather the data needed for the study. Based on initial information gathered through observation, interview and time studies conducted on the packing, wafer production and biscuit production lines of the company, several problems were identified. The main problems identified were insufficient equipment and tools, no definite worker assignment and priorities and no standards in conducting work. This resulted to a lot of scrap and worker idle time that hinders the company from reaching its full productive capacity. Focusing on these problems, several recommendations were proposed. Major recommendations were a more standardized system of shifting and job rotation within the different lines, enforcement of certain protocols in performing tasks, and modification and addition to existing equipment and tools that would aid in worker performance. A proposed schedule for the implementation of the proposed changes was also done based on analysis of the magnitude of the change and nature of each recommendation.